Trends in Artificial Intelligence for Power Grid Automation from an Academic Viewpoint - Guarnizo Marín, José Guillermo (Ingeniería, 2025)
Electric power networks are interconnected systems entrusted with transforming, transmitting, and distributing electricity from generation points to the end user. Within this architecture, electrical substations perform the intermediate function of voltage transformation and help to ensure power quality through appropriate control and protection systems. Accordingly, they require automation technologies that enable the continuous monitoring, control, and protection of the infrastructure involved in these processes. Although there are international standards for grid-automation processes—most notably IEC 61850 for communications [1]—, current advances in artificial intelligence (AI) open a window of opportunity to enhance control responses to grid fluctuations.